Design of PLC–Visual Studio Communication using CX–Server Lite for Automation Tool’s Crib - Pohan, Fredrico Aditrio; Santoso, Ari; Arifin, Imam; Zurqi, Ayyasy Az; Hady, Moh. Abdul (Institut Teknologi Sepuluh Nopember, 2019)
Role of tool’s in enterprise is important, because a machine cannot assembled if one of tool’s is not available. The problem that occured during transaction prosses of tools due to lack of information about the availability of tools, so the operator spend some time for searching the tools and the borrower is waiting for the operator. To solve this problem, a new system of tool’s crib is requied for the tools storage. This system uses web as tools availability and uses PLC instead of operator. PLC is connected to PC using ethernet cable and programmed with Visual Studio as master. But in communication between PLC and HMI cannot communicate because PLC and HMI is a differend vendor, therefore requied an application to connected them. OPC is solution for of communication between PLC and Visual Studio because OPC is special to connected different hardware and software vendor. This OPC called CX – Server Lite from Omron. The previous system is changed to automatic and called Automation Tool’s Crib and gives the fastest time than tools crib approximately 90 secondwith this communication.